Response of soil physics properties to liquid organic fertilizer from liquid waste from tofu factories and banana tubers in ultisol - Siti Nurul Aidil Fitri; Adipati Napoleon; Bakri Bakri; Agus Hermawan; Alfarezi Athallah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
Productivity in ultisols was not only determined by mineral content, but was also influenced by the physical properties of the soil. Soil physical properties were soil properties that were determined by its constituent materials such as water content, bulk density, total pore space and permeability. The study aimed to determine the effect of the application of liquid organic fertilizer from tofu factory liquid waste on the physical properties of soil in ultisols. This research was designed using a Completely Randomized Design (CRD) with six treatment levels (control treatment, single fertilizers N, P, and K as recommended doses, 125 ml, 250 ml, 375 ml and 500 ml Liquid Organic Fertilizer (LOF) from tofu factory wastewater and banana tubers. Each treatment was repeated 4 times, so there were 24 experimental units. The results showed that LOF treatment had a significant effect on bulk density, total pore space, and permeability and had no significant effect on moisture content in field capacity of green mustard plants in ultisols. The highest value obtained in the LOF treatment is at a dose of 250 ml which had a field capacity water content value of 29.63%, bulk density 0.95 g/cm3, total pore space of 64.00% and soil permeability of 11.56 cm/hour.